THE ROLE OF LYMPH NODE METASTASIS IN EARLY GASTRITIS INDIVIDUALS FOLLOWING NONCURATIVE ENDOSCOPIC RESECTION: A SYSTEMATIC REVIEW AND META-ANALYSIS - Rostami, Masoumeh; Mazin Hadi Kzar; Zahraa Hamzaa Abd alzahraa; Ali Abdul Kadhim Ruhaima; Sarah A. Hamood; Alzahraa S. Abdulwahid; Sarmad Dheyaa Noori; Ahmed Hussien Alawadi; Ali Alsaalamy; Ban Saifuddin Mahmoud (Journal of Ayub Medical College Abbottabad, 2023)
Background: Recent studies suggest that individuals who underwent noncurative endoscopic resection for gastric cancer may require additional surgery. We conducted a comprehensive systematic review and meta-analysis to investigate the risk of lymph node metastasis in these cases. Methods: We comprehensively examined relevant literature by extensively reviewing electronic databases such as PubMed, Cochrane Library, and Google Scholar. Subsequently, we analyzed clinicopathological outcomes and calculated pooled odds ratios and 95 percent confidence intervals using diverse effects models. Results: This analysis included 12 papers with 4808 individuals who underwent additional surgery after noncurative endoscopic resection for early gastric cancer. The results indicated significant associations between lymph node metastasis and submucosal invasion (Odd ratio 2.04, 95% (CI): 1.58-2.63, I 2 = 88.7%; p<0.001), vertical margin (Odd ratio 6.11, 95% (CI): 1.94-19.23, I 2 = 0%; p<0.001), lymphatic invasion (Odd ratio 10.02, 95% (CI): 7.57-13.27, I 2 = 92%; p<0.000), and vascular invasion (Odd ratio 7.11, 95% (CI): 5.49-9.22, I 2=92%; p<0.000). Conclusion: When choosing factors for surgical treatment, it is essential to thoroughly consider the invasion of lymph nodes, vascular system, submucosa, and positive vertical margin.